Carbohydrate Derived Non-ionic Gemini Surfactants: A Mini Review - Saroj; Sharma, Lalit (Mini-Reviews in Organic Chemistry, 2018)
The carbohydrate derived non-ionic gemini surfactants have emerged as a result of our present day interest in environmentally compatible chemicals. The literature, including patents, describing the emerging area of carbohydrate derived non-ionic gemini surfactants is reviewed. The present review paper deals with synthesis, surface-active properties and biological properties of carbohydrate derived non-ionic gemini surfactants. The application of these surfactants in solubilization process, emulsification, nanotechnology, and gene and drug delivery systems has been described.
Keywords: non-ionic